The Relationship Of Mother's Knowledge With Composition To Feeding In Babies Aged 6-12 Months During The Covid -19 Pandemic At Yusmalinda Mangga Clinic, Mangga Village Kec. Stabat - Srinur Nilawati; Bagusda Kelana Putra; Indah Rahmaini Hayat; Dewi Andini; Ferry Tri Wahydi (Institute of Computer Science (IOCS), 2020)
Many mothers are afraid that their children will not get good nutrition because of the mother's lack of knowledge about complementary foods that are good for their babies, especially during the pandemic. So therefore A study was conducted to determine the relationship between mother's knowledge and the provision of complementary foods to infants aged 6-12 months during the COVID-19 pandemic, Yusmalinda Midwife Clinic, Mango Village, Kec. Stabat 2020. And also to know the giving of complementary food to babies aged 6-12 months during the covid -19 pandemic. The population taken in this study were mothers who had babies aged 6-12 months in the working area of the Yusmalinda Midwife Clinic, Mangga Village, Kec. Stabat as many as 35 people. In this study, the sampling technique was carried out using a total sampling technique of 35 people. The research instrument used in this study was in the form of a questionnaire or questionnaire made by the researcher himself. The results of this study indicate that the majority of mothers' knowledge is good as many as 21 respondents and the minority of mothers' knowledge is less as many as 5 respondents. The majority of complementary feeding for infants aged 6-12 months was given by 25 respondents and the minority was not given as many as 10 respondents. There is a relationship between mother's knowledge and complementary feeding to infants aged 6-12 months during the Covid-19 pandemic at the Yusmalinda Midwife Clinic, Mangga Village, Kec. Stabat Year 2020.